Ant venom immunotherapy in Australia: the unmet need. Issue 1 (7th July 2014) - Mullins, Raymond J; Brown, Simon G A
Summary: Jack jumper ant (JJA) venom allergy is an important cause of anaphylaxis in south‐eastern Australia. The efficacy and real‐world effectiveness of JJA venom immunotherapy (VIT) to prevent anaphylaxis in allergic patients are now well established, with an evidence base that is at least equivalent to that supporting VIT for allergy to other insect species. The tolerability and safety of JJA VIT are comparable with those of honeybee VIT.